2011
DOI: 10.1037/a0023874
|View full text |Cite
|
Sign up to set email alerts
|

The differential effects of interpersonal conflict from customers and coworkers: Trait anger as a moderator.

Abstract: Interpersonal conflict (IC) at work is a frequently experienced type of workplace mistreatment that has been linked to a host of negative workplace outcomes. Previous research has shown that IC can have differential effects based on source, but this has not yet been investigated in terms of customer IC versus coworker IC. To remedy this oversight in the literature, we used a multimethod, multitime point design to compare IC from customers and coworkers experienced by 75 call center employees. Primarily, we inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
110
2
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(118 citation statements)
references
References 89 publications
3
110
2
3
Order By: Relevance
“…Egregious client victimizations impair employee cognitive functioning (Rafaeli, Erez, Ravid, Derfler-Rozin, & Efrat-Treister, 2012) and are especially overwhelming and frustrating to caregivers due to the problems associated and lack of workable solutions (Hellzen et al, 1998). As a result, employees will lack the cognitive control resources necessary to focus attention on replacing their negative emotions with more positive ones (see Groth & Grandey, 2012;Sliter, Pui, Sliter, & Jex, 2011). In a qualitative study, psychiatric nurses described encountering patient-instigated victimizations that were so egregious that they deviated from what was considered by the nurses as normal or expected victimization behaviors for their work environment.…”
Section: Victimization and Forgivenessmentioning
confidence: 99%
“…Egregious client victimizations impair employee cognitive functioning (Rafaeli, Erez, Ravid, Derfler-Rozin, & Efrat-Treister, 2012) and are especially overwhelming and frustrating to caregivers due to the problems associated and lack of workable solutions (Hellzen et al, 1998). As a result, employees will lack the cognitive control resources necessary to focus attention on replacing their negative emotions with more positive ones (see Groth & Grandey, 2012;Sliter, Pui, Sliter, & Jex, 2011). In a qualitative study, psychiatric nurses described encountering patient-instigated victimizations that were so egregious that they deviated from what was considered by the nurses as normal or expected victimization behaviors for their work environment.…”
Section: Victimization and Forgivenessmentioning
confidence: 99%
“…The body of research on incivility and performance is limited, but consistent, with studies reporting a significant moderate negative relationship between the two (Sliter, Jex, Wolford, & McInnerney, 2010;Sliter, Pui, Sliter, & Jex, 2011;Sliter, Sliter, & Jex, 2012). Abusive supervision was found to be negatively related to supervisor rated job performance and to the formal appraisal processes in general (Harris, Kacmar, & Zivnuska, 2007).…”
Section: The Workplace Aggression and Job Performance Relationshipmentioning
confidence: 99%
“…Specifically, research has shown that coworker initiated workplace aggression leads to more personal outcomes such as depression, lower selfesteem, anger, and stress and anxiety (Frone, 2000;Bruk-Lee & Spector, 2006;Wittgenstein, 2013). Research has linked the experience of these behavioral and attitudinal outcomes to lower levels of performance as they act as a job demand on the individual (e.g., Jamal, 1984;Pflanz & Olge, 2006;Sliter et al, 2011). Furthermore, social undermining's items directly focus on the behaviors of coworkers, unlike the interpersonal conflict, incivility, and bullying scales which differentiate between the roles of the perpetrators (see Appendix A).…”
Section: The Terminological Diversity Problemmentioning
confidence: 99%
“…Examining the links trait anger has with task conflict, relationship conflict, and incivility has shown trait anger to correlate strongly and positively with incidents of conflict between coworkers and customers (Sliter, Pui, Sliter, & Jex, 2011;Fox, Spector, & Miles, 2001). Trait anger has also shown positive correlations with counterproductive work behaviors (Fox et al, 2001), task performance (Sliter et al, 2011), and job dissatisfaction (Fox & Spector, 1999 & Sivanathan, 2007).…”
Section: Trait Angermentioning
confidence: 99%
“…Trait anger has also shown positive correlations with counterproductive work behaviors (Fox et al, 2001), task performance (Sliter et al, 2011), and job dissatisfaction (Fox & Spector, 1999 & Sivanathan, 2007).…”
Section: Trait Angermentioning
confidence: 99%